Transforming Legacy Mainframe Systems with the Strangler Pattern 2.0 - Vishal Sharma, (Utilitas Mathematica, 2025)
As technology evolved from the age of industrialization to the age of information, and finally to this current age of AI, the average lifecycle of technology shrank from 10 to 6, and now it is 3 years. Therefore, the definition of “legacy” has shifted. Applications developed before 2010, especially those built on mainframe or outdated technologies, are increasingly seen as candidates for modernization. Mainframe transformation has been a top priority in financial services, because of its’ operational inefficiencies and high maintenance costs associated with mainframes when compared to modern distributed systems. Still, the majority of the core processing engines within financial services depend on Mainframe as the mission critical business rules are embedded in the code base. This embedded business rules complexity makes it challenging for transforming the system without disrupting the business continuity. The improved system moving away from monolith to capability driven design would enable significant reduction in time to market and the Opex cost. This paper illustrates an approach for transforming a legacy system leveraging Strangler Pattern, in conjunction with other off the shelf tool(s), test data management and other critical design aspects keeping business continuity in the center.